ICTs for Financial Services in Africa - Stefanski, Scott (World Bank, Washington, DC, 2014)
The second most populous continent in the world and with abundant natural resources, Africa continues to grow as the world's economy currently stands on shaky ground. However, steady GDP gains are sometimes obscured by the continent's economic, political and social problems. As Africa grows and becomes more tightly integrated with the global economy, its citizens and businesses increasingly need access to financial services tools that will allow them to compete. ICT is one avenue for increasing that access as ICT and financial services complement each other. ICTs allow for greater financial inclusion, and the financial services sector is a primary driver of communications and network technology. However, the financial services sector has distinct developmental challenges. Issues of trust, consumer protection, and network systemic risks that can slow the pace of progress require clear and strong regulations. The need for policy and regulatory development is made more difficult by the speed of technological change. Nevertheless, strategic intervention through policy or public investment can play a critical role in addressing the challenges faced by the financial services sector.